Firms' reactions to the crisis and their consequences for the labour market. Results of a company survey conducted in Austria - Claudia Kwapil (European Central Bank (ECB), 2010)
This article is based on the results of two company surveys - the first was conducted in 2007, before the recession 2008/2009 hit Austria, and the second was conducted in 2009 shortly after the trough of it. We analyse firms' reactions to the crisis and focus on their labour market relevant decisions. Although base wages were cut more frequently than in economically calm times, wage reductions continued to be the exception rather than the rule. This indicates the existence of nominal wage rigidities in Austria. Instead of wage cuts, firms preferred to reduce working hours and to dismiss employees. We find that firm specific characteristics as well as characteristics of the workforce help explaining a firm's probability of dismissing employees. However, the force of the shock by which an individual firm is hit (during the 2008/2009 recession) does not influence the likelihood of dismissals.
Keywords: C25; E24; J30; 330; demand shock; Micro Survey Data; wage rigidity; Gesamtwirtschaftliche Nachfrage; Schock; Lohnrigidität; Beschäftigungseffekt; Österreich